Morphological Variations of Amorphophallusspp. Blume ex Decne. in Peninsular Malaysia - Surisa, Phornvillay; Siti Hajar, Ahmad; N.A.P., Abdullah; Rosenani, Abu Bakar; Nur Khairina, Yusof; N.A.M, Rashid (Society of Education, India, 2015)
Amorphophallus has attracted much attention as it contains glucomannan and also possessother medicinal properties. Prior to the collection of propagating materials and cultivation, identification and diversity information of the Amorphophallus species areessential as different species perform differently under cultivation. Sixty accessions of Amorphophallusspp., with 10accessions representing six locations, were used to assess morphological of vegetative characters variations. Thirty-four morphological characters of each accession were observed and recorded. Cluster and principal coordinate analysis using Gower’s similarity coefficient classified the accessions into two groups. The first group included all 10 accessions. The second group consisted of 50 accessions. The component analysis (PCA) results revealed the diversity among 60 Amorphophallus spp. accessions with the first three principal components contributed 66.34% of the total variability. The PCA show that there were variationsinmorphological characteristics among accessions of Amorphophallus spp. basedon corm size, corm shape, cormel number per corm and petiole nature. The morphological analysis results suggest that two different species, A. paeoniifoliusandA. prainii,were identified.